A novel prognostic model based on three clinic-related miRNAs for prostate cancer - Che, Ping; Jiang, Shihao; Zhang, Weiyang; Zhu, Huixuan; Hu, Daorong; Wang, Delin (Frontiers in Surgery, 2022)
Background: Prostate cancer (PCa) is the second most common malignant tumor in men worldwide. MiRNAs have been reported to play significant roles in prognosis prediction for patients with malignant tumors. Methods: The survival-related miRNAs (sDMIRs) were identified by COX regression analysis. The risk score model (RSM) was established based on three sDMIRs. The expression levels of sDMIRs in cell lines and clinical samples were detected via qPCR. The correlations between sDMIRs and clinicopathological characteristics of PCa patients were evaluated using the chi-square test and Fisher’s exact probability method. Results: Four sDMIRs were remarkably related to the prognosis of PCa patients based on univariate COX analysis, of which miR-10a-5p, miR-20a-5p and miR-508-3p were used to establish the RSM. The OS in the low-risk group was better than that in the high-risk group. In the verification of various prostate cell lines and clinical samples from 162 PCa patients, the prominently higher expression of miR-10a-5p and miR-20a-5p and lower expression of miR-508-3p were detected in PCa cell lines and tumor tissues, especially the more advanced T-stage. Besides, the higher expression of miR-20a-5p and miR-10a-5p was significantly correlated to the higher level of PSA, Gleason score, and the more advanced T-stage and distant metastasis status. Conclusion: We identify and validate the clinical significance of three sDMIRs and establish a verified RSM to evaluate prognosis for PCa patients. The findings not only provide a reliable tool for clinical decision-maker to evaluate patients prognosis, but also offer a novel perspective into the field of biomarkers identification.